The Effectiveness of Movement Control Order (MCO) in Curbing COVID-19 Cases in Malaysia - Amirul Ameer Md Haris; Tan Wei Ming (USIM Press, 2024)
Conference Date: 7th October 2021 https://nhs2021.usim.edu.my